Flexible Multi-Tier Dispute Resolution in International Tax Disputes. - Pistone, Pasquale (IBFD Publications USA, Incorporated, 2021)
This book is the first of its kind to abridge the whole phenomenon of cross-border tax disputes, from their prevention to their settlement.